Rural Development Experiences to Improve Rural Settlement in Iraq (1951-2024) (Journal of Planner and Development, 2025)
The research primarily targeted Iraqi experiences in rural development to improve rural stability, as rural stability is a pivotal element in the progress of societies. Rural development plays an important role in achieving this stability by raising the standard of living, providing job opportunities, developing basic facilities, and supporting community participation. The research addressed the most prominent impacts of the Iraqi experience in the scope of rural development and rural stability. The research aims to identify the most prominent characteristics of the Iraqi experience and employ them within the framework of rural stability, study and analyze the developments that occurred in rural stability in Iraq during the period (1951-2024), and identify the factors influencing the development of rural stability. The research was based on the hypothesis that the Iraqi experience in achieving rural stability throughout the period (1951-2024) led to fundamental impacts on rural development patterns and the achievement of positive transformation of rural settlements. One of the most important conclusions achieved is the role of development projects and their contribution to rural development of rural settlements and providing them with public social services (health and education) and technical and economic services to serve the agricultural reality, while applying modern methods of water rationing (such as fixed and pivot sprinklers) that support the rural economy. One of the most important recommendations was the need to integrate irrigation projects, housing, and basic services into integrated plans to ensure rural stability and reduce migration.